2002
DOI: 10.1038/sj.mp.4001041
|View full text |Cite
|
Sign up to set email alerts
|

Allelic association of the neuronal nitric oxide synthase (NOS1) gene with schizophrenia

Abstract: Nitric oxide (NO) has been identified as a widespread and multifunctional biological messenger molecule in the central nervous system (CNS), with possible roles in neurotransmission, neurosecretion, synaptic plasticity, and tissue injury in many neurological disorders, including schizophrenia. Neuronal NO is widely produced in the brain from L-arginine catalyzed by neuronal NO synthase (NOS1). We therefore hypothesized that the NOS1 gene may play a role in the pathophysiology of schizophrenia. In the present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
3
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 43 publications
1
76
3
2
Order By: Relevance
“…Titles and abstracts were scrutinized to exclude non-genetic studies, reducing the number of included studies to Costain et al, 2010;Fang et al, 2008;Greenwood et al, 2011;Husted et al, 2010;Kremeyer et al, 2009;Miranda et al, 2006;Nicodemus et al, 2008;Wratten et al, 2009) and one on NOS1 (Fallin et al, 2005), presented family-based, but not case-control data and were therefore not integrated in the meta-analysis for methodological reasons. The remaining studies on NOS1AP (n=6; (Aberg et al, 2010;Delorme et al, 2010;Nicodemus et al, 2010;Puri et al, 2007;Puri et al, 2006;Zheng et al, 2005)) and NOS1 (n=14; (Cui et al, 2010;Donohoe et al, 2009;Kawohl et al, 2008;Nicodemus et al, 2010;O'Donoghue et al, 2012;Okumura et al, 2009;Reif et al, 2006;Reif et al, 2011;Riley et al, 2010;Rose et al, 2012;Shinkai et al, 2002;Silberberg et al, 2010;Tang et al, 2008;Wang et al, 2012)) reported on case-control association data and were scrutinized in greater detailed. For NOS1AP, two and for NOS1, 11 further studies had to be excluded from meta-analysis for the following reasons.…”
Section: Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Titles and abstracts were scrutinized to exclude non-genetic studies, reducing the number of included studies to Costain et al, 2010;Fang et al, 2008;Greenwood et al, 2011;Husted et al, 2010;Kremeyer et al, 2009;Miranda et al, 2006;Nicodemus et al, 2008;Wratten et al, 2009) and one on NOS1 (Fallin et al, 2005), presented family-based, but not case-control data and were therefore not integrated in the meta-analysis for methodological reasons. The remaining studies on NOS1AP (n=6; (Aberg et al, 2010;Delorme et al, 2010;Nicodemus et al, 2010;Puri et al, 2007;Puri et al, 2006;Zheng et al, 2005)) and NOS1 (n=14; (Cui et al, 2010;Donohoe et al, 2009;Kawohl et al, 2008;Nicodemus et al, 2010;O'Donoghue et al, 2012;Okumura et al, 2009;Reif et al, 2006;Reif et al, 2011;Riley et al, 2010;Rose et al, 2012;Shinkai et al, 2002;Silberberg et al, 2010;Tang et al, 2008;Wang et al, 2012)) reported on case-control association data and were scrutinized in greater detailed. For NOS1AP, two and for NOS1, 11 further studies had to be excluded from meta-analysis for the following reasons.…”
Section: Meta-analysismentioning
confidence: 99%
“…For the NOS1 gene: (Kawohl et al, 2008;O'Donoghue et al, 2012;Rose et al, 2012) analysed exclusively healthy participants. (Donohoe et al, 2009;Nicodemus et al, 2010;Riley et al, 2010) and (Shinkai et al, 2002) only presented data on SNPs which have not been genotyped for the present study; no SNP data could be obtained from the study of (Wang et al, 2012); and the study by (Silberberg et al, 2010) was excluded because of the rather small sample size (n=26) precluding meaningful interpretation of the data. Finally, (Reif et al, 2011) and (Reif et al, 2006), were excluded because the case samples of both studies overlapped with the sample described here (while the control sample was extended more than two-fold).…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility that a dysfunctional NO system is involved in this disease is strengthened by studies showing an abnormal distribution of nitrinergic neurons in the frontal and temporal lobes of schizophrenic patients, which may reflect that the normal pattern of neuronal migration during development of the cerebral cortex may be affected in these patients (Akbarian et al, 1993a, b). More recent studies show that polymorphisms in the nNOS gene are associated with schizophrenia and PFC function in schizophrenic patients (Shinkai et al, 2002;Reif et al, 2006). In addition, two recent studies show a significant increase of NO metabolites in the serum of schizophrenic patients indicating that NO function may be dysregulated in this disorder (Taneli et al, 2004;Yilmaz et al, 2007) even if the interpretation of these findings is complicated by earlier studies showing a decrease in NO activity (Srivastava et al, 2001;Suzuki et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Four association studies were published investigating a synonymous, exonic single nucleotide polymorphism (SNP) in exon 29 (which codes for the last 4 amino acids of the translated protein and the 3 0 -UTR), or an SNP in intron 29 of NOS1 in SCZ and depression. The first study, including 200 patients, reported an association of NOS1 with SCZ, 40 while a replication study including 200 subjects was negative. 41 Another association study aiming at BPD failed to detect association as well, 42 as did another report on MD.…”
Section: Introductionmentioning
confidence: 99%